Medicine and the Humanities - Gordon, Michael (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
In the earliest writing of stories, physicians and illnesses often played an important role. Some of the renowned scholars in the Jewish tradition, like Moses Maimonides was a philosopher, a prolific writer, and a physician. A few of the world-famous authors include: François Rabelais (1483-1553), Anton Chekhov (1860-1904), Arthur Conan Doyle (1859-1930), Oliver Sacks (1933-2015) and the contemporary Abraham Verghese (1955-), to name just a few. The connection between medicine and the humanities appears to have diminished in some domains due partially to the focus on the scientific advances in medicine and the diminished focus on the humanities, especially in higher education. This I suggest, is a problem for medicine.